Librarians and Academics Building Capacity on Research Impact and Metrics for Creative Disciplines. Issue 3 (3rd July 2019) - Zhao, Linlin; Minns, Marina
ABSTRACT: In 2018, Deakin University Library Research Services Team and Faculty of Arts and Education Liaison Team developed a series of four capacity-building workshops on research impact and metrics for the academic staff in the School of Communication and Creative Arts, in collaboration with the Associate Head of School (Research). As part of the Library's Research Metrics and Advisory Service (ReMAS), the workshops were designed as the initial step of a long-term approach to meet the unique needs of academics in the creative disciplines, including visual arts, performing arts, creative writing, design, media and journalism. Using an autoethnographic approach, the paper examines, through critical reflections from the two key librarians involved, the impact of these workshops within the Library and among the academic community, including: facilitating academic capacity-building on research impact and metrics in creative disciplines, building internal and external collaborative relationships, and developing the Library's knowledge of and skills in designing tailored research impact and metrics services for researchers with non-traditional outputs.